The occurrence of childhood trauma in patients with severe mental illness with and without co-occurring substance disorders - Hector, Marc (Department of Psychiatry and Mental Health, 2022)
Background Childhood trauma (CT) has been associated with development of substance use disorders (SUDs) and severe mental illness (SMI) in community cohorts. There is a paucity of data on correlates of CT in dually diagnosed clinical populations in South Africa. We investigated the association among mono-substance use, polysubstance use and CT. Additionally, we explored demographic and clinical correlates of CT. Study aims We investigated associations between CT and SUD in patients with SMI. Setting Participants included patients aged 18–59 years with psychotic disorders attending specialist psychiatric hospital. Methods A cross-sectional study was conducted and the structured clinical interview for DSM-IV, (SCID – I) to determine SUD and SMI, and the childhood trauma questionnaire (CTQ) to measure CT were administered. Results Of the 74 patients, the mean age was 29 years (SD = 8.6) and 64% were male; 64% had schizophrenia-spectrum diagnoses, 23% had BMD-I and 14% had SIPD. Of the patients, 41% were taking no drugs, 22% were mono-drug users and 38% were poly-drug users. There was no significant difference between substance use groups in terms of age or level of education. However, those with no SUDs were significantly more likely to be female, whereas those with mono- or-poly-substance use were significantly more likely to be male. Patients with poly-SUD were significantly less likely to have been married and significantly more likely to have had a diagnosis of SIPD. There were no significant differences in CTQ scores by SUD groups. In this sample of patients with SMI, we found no significant association between CT and SUDs. Conclusion More research is needed into the effects CT has on dual diagnoses to inform treatment approaches to explore traumatic experiences.